Posttransplant Lymphoproliferative Disease after Pediatric Solid Organ Transplantation. (24th September 2013) - Mynarek, Martin; Schober, Tilmann; Behrends, Uta; Maecker-Kolhoff, Britta
Abstract : Patients after solid organ transplantation (SOT) carry a substantially increased risk to develop malignant lymphomas. This is in part due to the immunosuppression required to maintain the function of the organ graft. Depending on the transplanted organ, up to 15% of pediatric transplant recipients acquire posttransplant lymphoproliferative disease (PTLD), and eventually 20% of those succumb to the disease. Early diagnosis of PTLD is often hampered by the unspecific symptoms and the difficult differential diagnosis, which includes atypical infections as well as graft rejection. Treatment of PTLD is limited by the high vulnerability towards antineoplastic chemotherapy in transplanted children. However, new treatment strategies and especially the introduction of the monoclonal anti-CD20 antibody rituximab have dramatically improved outcomes of PTLD. This review discusses risk factors for the development of PTLD in children, summarizes current approaches to therapy, and gives an outlook on developing new treatment modalities like targeted therapy with virus-specific T cells. Finally, monitoring strategies are evaluated.